The EF English Proficiency Index and English in Ecuador: Uncertain assumptions of the international ranking - De Angelis, Adeline (2022)
Ecuador’s abysmal level of English according to the EF English Proficiency Index has become a habitual reference point when discussing English learning in Ecuador. This essay questions three assumptions implied by this international ranking: that it represents Ecuador’s language proficiency; that it offers a meaningful comparison between countries; and that concern for language proficiency is equivalent to concern for equity. Inspired by critical studies of international large-scale assessments, the principle that quantitative data is not neutral, and the concept that the index represents a discourse, I argue that this index is not as objective or trustworthy as it may appear and that the authority it is granted is worrisome for Ecuadorian education.